Catalytic, Enantioselective Synthesis of Stilbene cis-Diamines: A Concise Preparation of (–)-Nutlin-3, a Potent p53/MDM2 Inhibitor - Davis, Tyler A. (2011)
The first highly diastereo- and enantioselective additions of aryl nitromethane pronucleophiles to aryl aldimines are described. Identification of an electron rich chiral Bis(Amidine) catalyst for this aza-Henry variant was key to this development, leading ultimately to differentially protected cis-stilbene diamines in two steps. This method then became the lynchpin for an enantioselective synthesis of (–)-Nutlin-3 (Hoffmann-LaRoche), a potent cis-imidazoline small molecule inhibitor of p53-MDM2 used extensively as a probe of cell biology and currently in drug development.